2017
DOI: 10.1039/c6sm02262f
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and aggregation behaviour of an UCST-type copolymer poly(acrylamide-co-acrylonitrile) in water: effect of acrylonitrile content, concentration in solution, copolymer chain length and presence of electrolyte

Abstract: An UCST-type copolymer of acrylamide (AAm) and acrylonitrile (AN) (poly(AAm-co-AN)) was prepared by reversible addition fragmentation chain transfer (RAFT) polymerization and its temperature-induced phase transition and aggregation behaviour studied by turbidimetry, static and dynamic light scattering, small angle neutron scattering (SANS) and cryo-transmission electron microscopy (cryo-TEM) measurements. The phase transition temperature was found to increase with increasing AN content in the copolymer, concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 61 publications
7
87
2
1
Order By: Relevance
“…RAFT polymerization was then performed using Aam and AN as monomer, AIBN as initiator and HBPO-DTBA as RAFT agent (Figure 7). In contrast to the report of Asadujjaman et al [34], the UCST of this novel hyperbranched polymer can be increased by decreasing the arm (chain) length due to its unique molecular topology [39]. Synthesis of an ABA type triblock copolymers using P(AAm-co-AN) as outer blocks or middle block and hydrophilic poly(poly(ethylene glycol) methyl ether methacrylate) (PPEGMMA) and poly (N,N-dimethylacrylamide-co-7-acryloyl-4-methylcoumarin) as middle block and outer block, respectively, have also been reported [40,41].…”
Section: Poly(acrylamide-co-acrylonitrile)contrasting
confidence: 70%
See 1 more Smart Citation
“…RAFT polymerization was then performed using Aam and AN as monomer, AIBN as initiator and HBPO-DTBA as RAFT agent (Figure 7). In contrast to the report of Asadujjaman et al [34], the UCST of this novel hyperbranched polymer can be increased by decreasing the arm (chain) length due to its unique molecular topology [39]. Synthesis of an ABA type triblock copolymers using P(AAm-co-AN) as outer blocks or middle block and hydrophilic poly(poly(ethylene glycol) methyl ether methacrylate) (PPEGMMA) and poly (N,N-dimethylacrylamide-co-7-acryloyl-4-methylcoumarin) as middle block and outer block, respectively, have also been reported [40,41].…”
Section: Poly(acrylamide-co-acrylonitrile)contrasting
confidence: 70%
“…It was proposed that by changing the molar ratio of hydrophobic AN in Poly(AAm-co-AN), the UCST of polymer can be tuned easily ( Figure 4) [33]. Later, Asadujjaman et al [34] suggested that Poly(AAm-co-AN) with AN content between 0.086 to 0.221 only demonstrate UCST behavior with cloud point ranging from 5.5 to 56.5°C at 1 mg/ml concentration in water. This report suggested that the phase transition temperature (T pt ) increases with increase in AN content in the copolymer, increasing polymer concentration and polymer chain length and by addition of 300 mM Na 2 SO 4 in solution.…”
Section: Poly(acrylamide-co-acrylonitrile)mentioning
confidence: 99%
“…Above the UCST, there is rapid dissociation of hydrogen bonds and AAc‐AAm units, often referred to as a “zipper effect” resulting in solubilization of the individual units and dramatic swelling . Molecular chain modifications and copolymerization can also affect the stability and the swelling characteristics of these UCST hydrogels . In addition, ionic interactions can also be utilized to drive UCST behavior as in polybetaines.…”
Section: Principlesmentioning
confidence: 99%
“…[ 11–21 ] The non‐ionic polymers have attracted a great deal of attention due to their insensitivity to salts, which make them more attractive for applications in physiological environment. [ 22–24 ] During the last decade, efforts have been focused toward developing novel water‐soluble copolymers exhibiting UCST behavior by copolymerizing H‐donor monomers ( N ‐acryloyl glycinamide [ 11–16 ] or acrylamide [ 15,17–21,25 ] ) and H‐acceptor monomers (acrylonitrile, [ 11,15,18,19,21,25,26 ] styrene, [ 15,17 ] and butyl acrylate [ 15 ] ). Such (co)polymers have been mainly prepared using free radical polymerization [ 11,14–17,26 ] and by thermally initiated controlled radical polymerization such as atom transfer radical polymerization [ 13 ] and reversible addition fragmentation chain transfer (RAFT) [ 11,12,16–19,25 ] The impacts of various parameters on the UCST phase transition, including salts, pH, molecular weight, molecular weight distribution, and chemical composition, have been well evaluated.…”
Section: Figurementioning
confidence: 99%
“…Such (co)polymers have been mainly prepared using free radical polymerization [ 11,14–17,26 ] and by thermally initiated controlled radical polymerization such as atom transfer radical polymerization [ 13 ] and reversible addition fragmentation chain transfer (RAFT) [ 11,12,16–19,25 ] The impacts of various parameters on the UCST phase transition, including salts, pH, molecular weight, molecular weight distribution, and chemical composition, have been well evaluated. [ 7–9,25,27 ] However, such studies were carried out at low polymer concentrations (below 5 wt%). This could induce, an unintentional confusion between the UCST and the apparent cloud point temperature ( T CP ), which refers to the temperature at which the phase transition occurs depending on the investigated concentration level.…”
Section: Figurementioning
confidence: 99%